2008
DOI: 10.1002/anie.200703159
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Metalloenzymes for Asymmetric Allylic Alkylation on the Basis of the Biotin–Avidin Technology

Abstract: Dedicated to Professor Dieter Seebach on the occasion of his 70th birthdayPalladium-catalyzed CÀC bond-forming reactions play a prominent role in the construction of complex organic molecules. [1][2][3][4] As this versatile precious metal is absent in natural enzymes, nature has devised very different strategies to create C À C bonds for the construction of complex natural products. [5][6][7] The palladium-catalyzed asymmetric allylic alkylation (AAA) is a CÀC bond-forming reaction that has attracted much atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 60 publications
0
57
0
1
Order By: Relevance
“…This insight led to an expansion of Ward's research ranging from asymmetric transfer hydrogenation of prochiral ketones and imines, catalyzed by d 6 piano-stool complexes (Scheme 2); [12] and palladiumcatalyzed asymmetric allylic alkylation (Scheme 3) [13] towards oxidation reactions including the vanadyl-catalyzed sulfoxidation of prochiral sulfides (Scheme 4) [14] and the dihydroxylation of olefins.…”
Section: Artificial Metalloenzymes: Enantioselective Catalysis and Bementioning
confidence: 99%
“…This insight led to an expansion of Ward's research ranging from asymmetric transfer hydrogenation of prochiral ketones and imines, catalyzed by d 6 piano-stool complexes (Scheme 2); [12] and palladiumcatalyzed asymmetric allylic alkylation (Scheme 3) [13] towards oxidation reactions including the vanadyl-catalyzed sulfoxidation of prochiral sulfides (Scheme 4) [14] and the dihydroxylation of olefins.…”
Section: Artificial Metalloenzymes: Enantioselective Catalysis and Bementioning
confidence: 99%
“…Prior to our studies it was demonstrated that the chirality of DNA can be transferred in a stoichiometric DNA-templated reaction. [21][22][23] Furthermore, a DNAzyme capable of enantioselection of an RNA substrate [24] and an enantioselective Diels-Alderase RNAzyme have been reported. [25] In our approach to DNA-based enantioselective catalysis, [26][27][28] we have demonstrated that the chirality of DNA can be transferred directly to a metal-catalyzed reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] For the localization of an organometallic moiety within a macromolecular host, three anchoring strategies can be envisaged: covalent, dative or supramolecular. [5] Using such approaches, enantioselective artificial metalloenzymes have been created for hydrolysis, [12] hydrogenation, [14][15][16][17] transfer hydrogenation, [18] allylic alkylation, [19] sulfoxidation, [20][21][22][23][24] epoxidation, [25,26] dihydroxylation, [27] Diels-Alder, [28,29] trans-amination, [30] Michael addition [31] and fluorination. [32] Comparatively, supramolecular anchoring appears as the most appealing, since it allows separate variation of both biological and chemical components, followed by straightforward combination of the organometallic moiety and the macromolecular host.…”
mentioning
confidence: 99%